A proposed rural healthcare ethics agenda. Issue 3 (28th February 2007) - Nelson, W; Pomerantz, A; Howard, K; Bushy, A
Abstract : The unique context of the rural setting provides special challenges to furnishing ethical healthcare to its approximately 62 million inhabitants. Although rural communities are widely diverse, most have the following common features: limited economic resources, shared values, reduced health status, limited availability of and accessibility to healthcare services, overlapping professional–patient relationships and care giver stress. These rural features shape common healthcare ethical issues, including threats to confidentiality, boundary issues, professional–patient relationship and allocation of resources. To date, there exists a limited focus on rural healthcare ethics shown by the scarcity of rural healthcare ethics literature, rural ethics committees, rural focused ethics training and research on rural ethics issues. An interdisciplinary group of rural healthcare ethicists with backgrounds in medicine, nursing and philosophy was convened to explore the need for a rural healthcare ethics agenda. At the meeting, the Coalition for Rural Health Care Ethics agreed to a definition of rural healthcare ethics and a broad-ranging rural ethics agenda with the ultimate goal of enhancing the quality of patient care in rural America. The proposed agenda calls for increasing awareness and understanding of rural healthcare ethics through the development of evidence—informed, rural-attuned research, scholarship and education in collaboration with rural healthcare professionals, healthcare institutions and the diverse rural population.